The Production Cycle of Pisa Data in Brazil - Marialuisa Villani (Universidade de Lisboa, 2018)
We analyse the process of the production cycle of the OECD's Program for International Student Assessment (PISA) data in Brazil for 2012 and 2015 editions.  We present the qualitative data collected in 2016 through semi-structured interviews conducted with members of the Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira [National Institute for Educational Studies and Research] (INEP) who worked for PISA in Brazil for 2012 and 2015 editions. We made an ethnography of Brazilian PISA data to show the level of social embeddedness of statistics. In this paper, we propose a mindful approach to statistical data, particularly when results of international large-scale assessments (ILSA) are used to describe an educational system as complex as the Brazilian one. It is possible identify several levels of governance in PISA data production. That produces gap and misalignments that have an impact on quality of information disseminated by PISA data in Brazil.